2019
DOI: 10.1186/s40851-019-0128-0
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic of plesiomorphic and derived characters in an Eocene myliobatiform batomorph (Chondrichthyes, Elasmobranchii) from Italy defines a new, basal body plan in pelagic stingrays

Abstract: Background End-Cretaceous niche-filling by benthic Mesozoic survivors resulted in a prominent increase of durophagous fish families, resulting in the appearance of the earliest representatives of several extant fish lineages, including the pelagic durophagous stingrays, a monophyletic clade of myliobatiform batoids that is characterized by a derived swimming mode and feeding habits. Although the earliest members appeared in the Late Cretaceous, most of the crown genera date back to the Eocene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
1
11
1
Order By: Relevance
“…8a). The tree is consistent with those depicted in recent studies on Bolca stingrays 6,13 . The monophyly of the Myliobatiformes, as recognized by several authors 3,4,49,50 , is confirmed and supported herein (Bremer value 4) by ten characters: basihyal as a single element, but separated from the first hypobranchials (ch.…”
Section: Descriptionsupporting
confidence: 91%
See 3 more Smart Citations
“…8a). The tree is consistent with those depicted in recent studies on Bolca stingrays 6,13 . The monophyly of the Myliobatiformes, as recognized by several authors 3,4,49,50 , is confirmed and supported herein (Bremer value 4) by ten characters: basihyal as a single element, but separated from the first hypobranchials (ch.…”
Section: Descriptionsupporting
confidence: 91%
“…Like in many other studies primarily based on morphological data 3,4,6,13,45 , the sixgill stingray Hexatrygon is inferred to be the sister to all other stingrays, although this contrasts with recent molecular phylogenies, where Hexatrygon is recovered as sister to Gymnura 16 or to urolophids 51,52 . The present study detected again a dichotomy of the remaining Myliobatiformes, in which the nature of the two main clades (Myliobatoidea and Dasyatoidea) can be possibly linked to the different calcifications of radial cartilages, body shape, swimming mode and life style 48 .…”
Section: Descriptioncontrasting
confidence: 46%
See 2 more Smart Citations
“… 2016 , 2019 ; Marramà et al . 2018a , b , c , 2019a , b , c, d ;). These batoids are represented by electric rays (Torpediniformes), guitarfishes (Rhinopristiformes), stingrays (Myliobatiformes) and three batoid species that were historically assigned to the thornback ray genus Platyrhina Müller & Henle, 1838 : † P. bolcensis Heckel, 1851 , † P. egertoni (De Zigno, 1876 ) and † P. gigantea (Blainville, 1818).…”
Section: Introductionmentioning
confidence: 99%